Suppressing aflatoxin biosynthesis is not a breakthrough if not useful. Issue 1 (5th September 2017) - Gressel, Jonathan; Polturak, Guy
Abstract : Will transiently suppressing aflatoxin synthesis enhance the value of moldy grain? Abstract: Liver‐affecting, carcinogenic aflatoxins produced by Aspergillus spp. are a major problem, especially in the humid developing world where storage conditions are often optimal for the fungi. Peanuts and maize have been transformed with RNAi constructs targeting Aspergillus flavus polyketide‐synthase, an early key enzyme in aflatoxin biosynthesis. Aflatoxin biosynthesis was suppressed in developing immature grain, less so in late maturing grain, and it is doubtful that the technology will be effective in near dry mature grain. The infected grain was still mouldy. As Aspergillus that infects grain preharvest can continue to grow and produce aflatoxin in poorly stored grain, and grain storage insects vector further infections, this technology seems to have little potential utility in the humid tropics. The biotechnological approaches of RNAi directly targeting Aspergillus, coupled with transgenic insecticidal proteins should be far more effective. These biotechnological approaches can be used in tandem with the RNAi against polyketide‐synthase, as well as with irradiation, biocontrol and better grain drying and hermetic dry storage in a controlled atmosphere. © 2017 Society of Chemical Industry